2017
DOI: 10.3389/fphar.2017.00432
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Supplementation Therapy for Pathological Neonatal Jaundice: A Systematic Review and Meta-Analysis

Abstract: Background: Neonatal jaundice is a relatively prevalent disease and affects approximately 2.4–15% newborns. Probiotics supplementation therapy could assist to improve the recovery of neonatal jaundice, through enhancing immunity mainly by regulating bacterial colonies. However, there is limited evidence regarding the effect of probiotics on bilirubin level in neonates. Therefore, this study aims at systematically evaluating the efficacy and safety of probiotics supplement therapy for pathological neonatal jaun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 18 publications
2
32
1
Order By: Relevance
“…However, due to the single time point of sample collection in this study, we could only confirm the correlation between B. pseudolongum and ɑ-diversity, but not causality. We should notice that clinicians are using probiotic supplementation including Bifidobacterium to prevent and treat neonatal jaundice around the world 29 . Two meta-analyses on randomized controlled trials of probiotics therapy for the management of neonatal jaundice conservatively concluded that probiotic supplementation could be effective in treating neonatal jaundice 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the single time point of sample collection in this study, we could only confirm the correlation between B. pseudolongum and ɑ-diversity, but not causality. We should notice that clinicians are using probiotic supplementation including Bifidobacterium to prevent and treat neonatal jaundice around the world 29 . Two meta-analyses on randomized controlled trials of probiotics therapy for the management of neonatal jaundice conservatively concluded that probiotic supplementation could be effective in treating neonatal jaundice 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…We should notice that clinicians are using probiotic supplementation including Bifidobacterium to prevent and treat neonatal jaundice around the world 29 . Two meta-analyses on randomized controlled trials of probiotics therapy for the management of neonatal jaundice conservatively concluded that probiotic supplementation could be effective in treating neonatal jaundice 29 , 30 . Large population-based longitudinal time-series studies are needed to confirm the causal association among B. pseudolongum , ɑ-diversity and neonatal jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…There are two widely accepted methods of neonatal jaundice treatment, phototherapy and blood exchange (Amiri et al, 2014 ; Chen et al, 2017 ). In addition, herbal remedies are also very popular in the treatment of jaundice, especially in the Iranian tradition (Rajaei and Mohamadi, 2012 ; Amiri et al, 2014 ).…”
Section: Ethnopharmacological Approaches For Management Of Jaundice: mentioning
confidence: 99%
“…Neonatal jaundice, presenting as yellow discoloration of the skin, sclera, and mucous membranes in infants and indicating raised serum bilirubin level, is one of the most common clinical conditions that may need medical attention (1). Unconjugated hyperbilirubinemia is the most common form of hyperbilirubinemia observed in neonates (2). Neonatal jaundice generally appears around two to four days after birth and vanishes one to two weeks later, often without the need for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Cumulatively, 24 million newborns develop jaundice every year (4). Approximately, 80% of preterm and 60% of term infants develop jaundice in the first week of life (2).…”
Section: Introductionmentioning
confidence: 99%